High-compaction lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

By mixing high-iron-phosphorus iron phosphate with different abrasive slurry particle sizes with low-iron-phosphorus iron phosphate and high-voltage iron phosphate, the problem of complex preparation methods and secondary sintering in the prior art is solved, and the preparation of high-capacity and high-pressure lithium iron phosphate positive electrode material is achieved, with the advantages of simple operation and low production cost.

CN119954124APending Publication Date: 2025-05-09HUNAN CHANGYUAN LICO NEW ENERGY CO LTD +2

Patent Information

Application Number
CN202510156129.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode material preparation method is complex and requires secondary sintering, resulting in unfavorable production.

Method used

High-pressure lithium iron phosphate positive electrode material is prepared by mixing high-voltage iron phosphate Fex'PO4 with different abrasive slurry particle sizes with low-voltage iron phosphate Fex'PO4 and sintering it in one sintering.

Benefits of technology

The preparation of high-capacity and high-pressure lithium iron phosphate positive electrode material is achieved, with simple operation and low production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954124A_ABST
    Figure CN119954124A_ABST
Patent Text Reader

Abstract

The invention provides a high-compaction lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of preparation of a lithium ion battery positive electrode material. The preparation method of the lithium iron phosphate positive electrode material comprises the following steps: mixing FexPO4 with a lithium source, a carbon source, an additive and water to obtain a first mixture, and sanding to obtain first slurry, x being 0.955-0.965; fexPO4 is mixed with a lithium source, a carbon source, an additive and water to obtain a second mixture, the second mixture is sanded to obtain second slurry, the particle size of the second slurry is larger than that of the first slurry, x 'is larger than x, and x' is 0.965-0.980; and carrying out spray drying and sintering on third slurry obtained by mixing the first slurry and the second slurry to obtain the lithium iron phosphate positive electrode material. According to the invention, iron phosphate with high iron-phosphorus ratio and iron phosphate with low iron-phosphorus ratio and different particle sizes are mixed for primary sintering, so that the compaction density of the positive electrode material can be improved, and the lithium iron phosphate positive electrode material with high compaction and high capacity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of positive electrode materials for lithium-ion batteries, and in particular to a high-density lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] As the cathode material of lithium-ion batteries, lithium iron phosphate has attracted much attention due to its high safety, long cycle life and excellent thermal stability. In recent years, with the rapid development of new energy vehicles, energy storage systems and portable electronic devices, the demand for high-performance and low-cost cathode materials has been growing.

[0003] Patent document CN114368737A discloses a high-density, high-capacity lithium iron phosphate positive electrode material and its preparation method and application. The document uses low-cost iron-resistant oxide raw materials for sintering to form primary crystal seeds. The primary crystal seeds have high-density characteristics, and then are mixed with iron phosphate, lithium carbonate, additives, and carbon sources for grinding, spray granulation, sintering and crushing. The primary crystal seeds promote the synthesis of lithium iron phosphate crystals from iron phosphate. This part of lithium iron phosphate has high capacity characteristics. After the primary crystal seeds undergo secondary heat treatment, the primary particles increase and the compaction density increases. In addition, the coating and doping modification of the lithium iron phosphate finished product are completed during the secondary heat treatment process, and finally a high-capacity and high-density lithium iron phosphate positive electrode material is synthesized. However, this method requires secondary sintering, and the preparation method is complicated, which is not conducive to actual production.

[0004] Therefore, it is necessary to improve the preparation method of lithium iron phosphate positive electrode material. Summary of the invention

[0005] The purpose of the present application is to provide a high-density lithium iron phosphate positive electrode material and a preparation method thereof and a lithium-ion battery to solve the above problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A method for preparing a high-density lithium iron phosphate positive electrode material, the preparation method comprising the following steps:

[0008] Fe x PO4 is mixed with a lithium source, a carbon source, an additive, and water to obtain a first mixture, and sand-milled to obtain a first slurry, wherein x is 0.955 to 0.965;

[0009] Fe x’ PO4 is mixed with a lithium source, a carbon source, an additive, and water to obtain a second mixture, and sand-milled to obtain a second slurry, wherein the particle size of the second slurry is greater than the particle size of the first slurry, x'>x, x' is 0.965 to 0.980, preferably 0.970 to 0.975;

[0010] Mixing the first slurry with the second slurry to obtain a third slurry;

[0011] The third slurry is spray-dried to obtain a lithium iron phosphate precursor yellow material;

[0012] The lithium iron phosphate precursor yellow material is sintered and crushed to obtain a high-density lithium iron phosphate positive electrode material.

[0013] According to an embodiment of the present application, the particle size of the first slurry is 0.35-0.45 μm, and the particle size of the second slurry is 0.45-0.55 μm, preferably 0.48-0.55 μm.

[0014] According to an embodiment of the present application, the lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide;

[0015] The carbon source includes a carbon-based material or a hydrate of a carbon-based material, and the carbon-based material includes at least one of PEG, citric acid, glucose, PVP, and sucrose;

[0016] The additive includes at least one of titanium dioxide, ammonium titanium oxalate, vanadium pentoxide, ammonium metavanadate, and manganese acetate, preferably titanium dioxide and ammonium titanium oxalate, and more preferably titanium dioxide.

[0017] According to an embodiment of the present application, when the first mixture is formed, the Li in the lithium source and the Fe x The molar ratio of Fe in PO4 is (1.0-1.1):1;

[0018] And / or, when forming the first mixture, the Fe x The mass ratio of PO4 to the carbon source is 1:(0.05-0.15), preferably 1:(0.09-0.11).

[0019] and / or, when forming the first mixture, the mass of the metal cations in the additive accounts for 100-3000 ppm, preferably 1500-3000 ppm, of the mass of the finished lithium iron phosphate material;

[0020] And / or, when forming the second mixture, the Li in the lithium source and the Fe x’ The molar ratio of Fe in PO4 is (1.0-1.1):1, preferably (1.03-1.1):1;

[0021] And / or, when forming the second mixture, the Fe x’ The mass ratio of PO4 to the carbon source is 1:(0.05-0.15), preferably 1:(0.09-0.11);

[0022] and / or, when forming the second mixture, the mass of the metal cations in the additive accounts for 100-3000 ppm, preferably 1500-3000 ppm, of the mass of the finished lithium iron phosphate material;

[0023] According to an embodiment of the present application, the mass ratio of the first slurry to the second slurry is (1-100):(100-1), preferably (30-40):(60-70).

[0024] According to an embodiment of the present application, the inlet air temperature of the spray drying is 180-280°C, and the outlet air temperature of the spray drying is 90-100°C.

[0025] According to an embodiment of the present application, the sintering includes: heating to a sintering temperature, keeping warm at the sintering temperature, and then cooling to room temperature, the sintering temperature is 700-800°C, preferably 770-800°C, preferably 790°C, the heating time is 5-9h, the keeping time is 7-10h, and the cooling time is 8-10h;

[0026] The sintering is performed in an inert atmosphere.

[0027] The present application provides a high-density lithium iron phosphate positive electrode material, and the high-density lithium iron phosphate positive electrode material is prepared by the preparation method of the high-density lithium iron phosphate positive electrode material described above.

[0028] The present application also provides a high-density lithium iron phosphate positive electrode material, which includes a first particle and a second particle, wherein the particle size of the first particle is less than or equal to 1 μm, and the particle size of the second particle is greater than 1 μm.

[0029] And / or, the volume ratio of the first particles to the second particles is (40-60):(60-40);

[0030] And / or, the first particle comprises Li 1.0-1.1 Fe x’ PO4, where x' is 0.965 to 0.980 ;

[0031] And / or, the second particle comprises Li 1.0-1.1 Fe x PO4, wherein x is 0.955 to 0.965.

[0032] In some embodiments, the high-density lithium iron phosphate positive electrode material including the first particles and the second particles is prepared by the preparation method described above.

[0033] The present application also provides a lithium-ion battery, which includes the high-density lithium iron phosphate positive electrode material described above.

[0034] Compared with the prior art, the beneficial effects of this application include:

[0035] The present invention relates to the high iron-phosphorus ratio of iron phosphate Fe of different grinding slurry particle sizes. x’ PO4 and low iron-phosphorus ratio iron phosphate Fe x PO4 after sintering once, a lithium iron phosphate positive electrode material with both high capacity and high compaction can be obtained. The method of the present application has the advantages of simple operation and low production cost. x’ PO4 is beneficial to improve the stability of the crystal structure and the capacity of the positive electrode material; low iron-phosphorus ratio iron phosphate Fe x The proportion of P in PO4 is relatively high, and the particle size of the first slurry prepared therefrom is relatively small, which is conducive to the formation of product particles with larger particle size by melting growth during the sintering stage. x’ The proportion of P in PO4 is low, and the particle size of the second slurry prepared therefrom is relatively large, which is conducive to the formation of product particles with smaller particle size during the sintering stage. The product particles with larger particle size cooperate with the product particles with smaller particle size, which can effectively improve the compaction density of the positive electrode material and obtain a high-compacted and high-capacity lithium iron phosphate positive electrode material.

[0036] The lithium iron phosphate positive electrode material of the present application can be applied to power batteries, which can improve the energy density of the battery cells and reduce the manufacturing cost of the battery cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0038] Figure 1 This is a comparison chart of particle size volume distribution of lithium iron phosphate positive electrode materials of Examples 1-5 of the present application and Comparative Examples 3 and 5;

[0039] Figure 2 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1;

[0040] Figure 3 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 2;

[0041] Figure 4 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 3;

[0042] Figure 5 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 4;

[0043] Figure 6 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 5;

[0044] Figure 7 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 2;

[0045] Figure 8 This is the SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 5. DETAILED DESCRIPTION

[0046] As used herein:

[0047] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0048] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0049] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0050] In these examples, parts and percentages are by mass unless otherwise indicated.

[0051] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0052] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0053] The present application provides a method for preparing a high-density lithium iron phosphate positive electrode material, the preparation method comprising the following steps:

[0054] Fe x PO4 is mixed with a lithium source, a carbon source, an additive, and water to obtain a first mixture, and sand-milled to obtain a first slurry, wherein x is 0.955 to 0.965;

[0055] Fe x’ PO4 is mixed with a lithium source, a carbon source, an additive, and water to obtain a second mixture, and sand-milled to obtain a second slurry, wherein the particle size of the second slurry is greater than the particle size of the first slurry, x'>x, x' is 0.965 to 0.980, preferably 0.970 to 0.975;

[0056] Mixing the first slurry with the second slurry to obtain a third slurry;

[0057] The third slurry is spray-dried to obtain a lithium iron phosphate precursor yellow material;

[0058] The lithium iron phosphate precursor yellow material is sintered and crushed to obtain a high-density lithium iron phosphate positive electrode material.

[0059] Fe x’ The iron-phosphorus ratio in PO4 is high, Fe 3+ The embedding effect in the material is obvious, which is beneficial to improve the stability of the material's crystal structure. 3+ Participating in the charge and discharge reaction can increase the current density and improve the rate performance and capacity of the positive electrode material. x PO4 has a low iron-phosphorus ratio. The higher the P ratio, the more excess P can promote particle growth. x The particle size of the first slurry of PO4 is relatively small. The smaller the particle size, the higher the activity. At the same temperature, the solid particles in the first slurry are more likely to fuse and grow into large particles. x’The particle size of the second slurry of PO4 is relatively large, and the solid particles in the second slurry are not easy to grow after sintering, and small particles are formed after sintering. The large particles and the small particles cooperate with each other, which can effectively improve the compaction density of the positive electrode material.

[0060] In this application, low iron-phosphorus ratio iron phosphate Fe x PO4 cooperates with smaller sand grinding particle size, which is conducive to the formation of large particles during the sintering stage; high iron phosphorus ratio iron phosphate Fe x’ PO4 and larger sanding particle size cooperate with each other, which is conducive to the formation of small particles in the sintering stage; large particles and small particles can optimize the particle size distribution, increase the packing density, increase the compaction density, and at the same time improve the dynamic performance to ensure the product capacity. After a single sintering process, the present application can obtain a lithium iron phosphate positive electrode material with both high capacity and high compaction. The present application has the advantages of simple operation and low production cost.

[0061] According to some embodiments of the present application, x may be 0.955, 0.956, 0.957, 0.958, 0.959, 0.960, 0.961, 0.962, 0.963, 0.964, 0.965 or any value between 0.955 and 0.965, and x' may be 0.965, 0.966, 0.967, 0.968, 0.969, 0.970, 0.971, 0.972, 0.973, 0.974, 0.975, 0.980 or any value between 0.965 and 0.980.

[0062] According to an embodiment of the present application, the particle size of the first slurry is 0.35-0.45 μm, and the particle size of the second slurry is 0.45-0.55 μm, preferably 0.48-0.55 μm. As a result, the solid particles in the first slurry have a smaller particle size and are easily melted and grown into large particles during sintering. Due to the limitations of sand milling equipment, the particle size of the first slurry cannot be infinitely small; if the particle size of the solid particles in the first slurry is too large, the activity will be reduced, which is not conducive to the growth of the particles; in addition, the large particle size of the solid particles in the second slurry is not conducive to uniform mixing of materials, and is not conducive to lithium embedding in the lattice.

[0063] When the particle size of the solid particles in the first slurry is 0.35-0.45 μm, and the particle size of the solid particles in the second slurry is 0.45-0.55 μm, preferably 0.48-0.55 μm, it is beneficial for the solid particles in the first slurry to form particles with larger particle size during sintering, and the solid particles in the second slurry to form particles with smaller particle size during sintering. The particles with larger particle size cooperate with the particles with smaller particle size, which is beneficial to obtain a high-density and high-capacity positive electrode material.

[0064] Furthermore, the sanding particle size can be controlled by adjusting parameters such as the zirconium balls used in the sanding and / or the sanding time.

[0065] According to some embodiments of the present application, the particle size of the first slurry may be 0.35 μm, 0.36 μm, 0.37 μm, 0.38 μm, 0.39 μm, 0.40 μm, 0.41 μm, 0.42 μm, 0.43 μm, 0.44 μm, 0.445 μm, 0.45 μm or any value between 0.35 and 0.45 μm, and the particle size of the second slurry may be 0.45 μm, 0.46 μm, 0.47 μm, 0.48 μm, 0.49 μm, 0.50 μm, 0.51 μm, 0.52 μm, 0.53 μm, 0.54 μm, 0.55 μm or any value between 0.45 and 0.55 μm.

[0066] According to an embodiment of the present application, the lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide;

[0067] The carbon source includes a carbon-based material or a hydrate of a carbon-based material, and the carbon-based material includes at least one of PEG, citric acid, glucose, PVP, and sucrose; these carbon-based materials have the advantage of low cost, which is beneficial to reducing the production cost of the method of the present application.

[0068] In some embodiments of the present application, the carbon source is preferably glucose or glucose monohydrate.

[0069] Furthermore, PEG includes PEG6000.

[0070] The additive includes at least one of titanium dioxide, ammonium titanium oxalate, vanadium pentoxide, ammonium metavanadate, and manganese acetate. The additive can improve the conductivity of the positive electrode material and accelerate the transmission speed of electrons and ions in the material. In addition, the additive can also inhibit particle growth and optimize capacity.

[0071] According to an embodiment of the present application, when the first mixture is formed, the Li in the lithium source and the Fe x The molar ratio of Fe in PO4 is (1.0-1.1):1;

[0072] For example, when forming the first mixture, Fe x The molar ratio of Fe in PO4 to Li in the lithium source can be 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1 or any value between 1:(1.0-1.1);

[0073] And / or, when forming the first mixture, the Fex The molar ratio of PO4 to the carbon source is 1:(0.05-0.15), preferably 1:(0.09-0.11).

[0074] For example, when forming the first mixture, Fe x The molar ratio of PO4 to the carbon source can be 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15 or any value between 1:(0.05-0.15).

[0075] and / or, when forming the first mixture, the mass of the metal cations in the additive accounts for 100-3000 ppm, preferably 1500-3000 ppm, of the mass of the finished lithium iron phosphate material;

[0076] For example, when the first mixture is formed, the mass of the metal cation in the additive accounts for 100 ppm, 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm or any value between 100-3000 ppm of the mass of the finished lithium iron phosphate material.

[0077] And / or, when forming the second mixture, the Li in the lithium source and the Fe x’ The molar ratio of Fe in PO4 is (1.0-1.1):1;

[0078] For example, when forming the second mixture, Fe x’ The molar ratio of Fe in PO4 to Li in the lithium source can be 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1 or any value between 1:(1.0-1.1).

[0079] And / or, when forming the second mixture, the Fe x’ The mass ratio of PO4 to the carbon source is 1:(0.05-0.15), preferably 1:(0.09-0.11);

[0080] For example, when forming the second mixture, Fe x’ The mass ratio of PO4 to the carbon source can be 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15 or any value between 1:(0.05-0.15).

[0081] and / or, when forming the second mixture, the mass of the metal cations in the additive accounts for 100-3000 ppm, preferably 1500-3000 ppm, of the mass of the finished lithium iron phosphate material;

[0082] For example, when the second mixture is formed, the mass of the metal cation in the additive accounts for 100 ppm, 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm or any value between 100-3000 ppm of the mass of the finished lithium iron phosphate material.

[0083] According to an embodiment of the present application, the mass ratio of the first slurry to the second slurry is (1-100): (100-1), preferably (30-40): (60-70), specifically 30:70 to 40:60, for example, including 30:70, 40:60, 50:50, etc. As a result, the first slurry is easy to grow into particles with larger particle size after sintering, and the second slurry is easy to grow into particles with smaller particle size after sintering. When the mass ratio of the first slurry to the second slurry meets the above conditions, the large and small particles cooperate with each other, which can effectively improve the compaction density of the positive electrode material. If the content of the first slurry is too much, there will be too many large particles and the compaction density will be low. At the same time, the stability of the crystal structure will be reduced, thereby reducing the electrochemical stability of the material and causing the material to have a lower capacity. If the content of the second slurry is too much, the compaction density will be low.

[0084] For example, the mass ratio of the first slurry to the second slurry may be 1:100, 30:70, 35:65, 40:60, 100:1, 1:1 or any value between (1-100):(100-1).

[0085] According to an embodiment of the present application, the inlet air temperature of the spray drying is 180-280° C., and the outlet air temperature of the spray drying is 90-100° C. Thus, water in the third slurry can be removed, reducing the adverse effects of water on the sintering equipment.

[0086] For example, the inlet air temperature of spray drying can be 180°C, 200°C, 230°C, 250°C, 280°C or any value between 180-280°C, and the outlet air temperature of spray drying can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C or any value between 90-100°C.

[0087] According to an embodiment of the present application, the sintering includes: heating to a sintering temperature, keeping warm at the sintering temperature, and then cooling to room temperature, the sintering temperature is less than 800°C, for example, 700°C to 800°C, preferably 770°C to 800°C, the heating time is 5 to 9 hours, the keeping time is 7 to 10 hours, the cooling time is 8 to 10 hours, and the sintering is carried out in an inert atmosphere.

[0088] For example, the sintering temperature may be 700° C., 710° C., 720° C., 730° C., 740° C., 750° C., 760° C., 770° C., 780° C., 790° C., 800° C., or any value between 700° C. and 800° C. When the sintering temperature is too high, the overall particle size of the particles produced by sintering will be too large, resulting in a lower compaction density and a simultaneous decrease in discharge capacity; when the sintering temperature is too low, the degree of crystallization of the material will be insufficient, the particle size will be low, and the material performance will be deteriorated.

[0089] The heating time can be 5h, 6h, 7h, 8h, 9h or any value between 5 and 9h, the insulation time can be 7h, 7.5h, 8h, 9h, 10h or any value between 7 and 10h, and the cooling time can be 8h, 9h, 10h or any value between 8 and 10h.

[0090] The present application also provides a high-density lithium iron phosphate positive electrode material, which is prepared by the preparation method of the high-density lithium iron phosphate positive electrode material described above.

[0091] The present application also provides a high-density lithium iron phosphate positive electrode material, the high-density lithium iron phosphate positive electrode material comprises a first particle and a second particle, the particle size of the first particle is less than or equal to 1 μm, and the particle size of the second particle is greater than 1 μm;

[0092] And / or, the volume ratio of the first particles to the second particles is (40-60):(60-40);

[0093] And / or, the first particle comprises Li 1.0-1.1 Fe x’ PO4, where x' is 0.965 to 0.980 ;

[0094] And / or, the second particle comprises Li 1.0-1.1 Fe x PO4, wherein x is 0.955 to 0.965.

[0095] The present application also provides a lithium-ion battery, which includes the high-density lithium iron phosphate positive electrode material described above.

[0096] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0097] Example 1

[0098] Embodiment 1 provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0099] (1) Fe x PO4, lithium source, carbon source and additives are added to water, the solid content is maintained at 40%, and homogenized and stirred in a dispersion tank, wherein x is 0.960, the lithium source is lithium carbonate, the carbon source is glucose monohydrate, and the additive is titanium dioxide, wherein the molar ratio of Li:Fe (Li in the lithium source and Fe in the carbon source) is 0.960. x The molar ratio of Fe in PO4 is 1.03:1, Fe x The mass ratio of PO4 to carbon source is 1:0.098, and the mass of Ti ions in the additive accounts for 2000ppm of the mass of the finished product LiFePO4. After being evenly dispersed, it is transferred to sand milling, and the average particle size of the sand milled slurry is maintained at 0.4μm to obtain the first slurry;

[0100] (2) Fe x’ PO4, lithium source, carbon source, and additives are added to water, the solid content is maintained at 40%, and homogenized and stirred in a dispersion tank, wherein x' is 0.972, the lithium source is lithium carbonate, the carbon source is glucose monohydrate, and the additive is titanium dioxide, wherein the molar ratio of Li:Fe (Li in the lithium source and Fe in the carbon source) is 0.972. x’ The molar ratio of Fe in PO4 is 1.03:1, Fe x’ The mass ratio of PO4 to carbon source is 1:0.098, and the mass of Ti ions in the additive accounts for 2000ppm of the mass of the finished product LiFePO4. After being evenly dispersed, it is transferred to sand milling, and the sand milling particle size is maintained at 0.5μm to obtain the second slurry;

[0101] (3) mixing the first slurry and the second slurry evenly in a finished product tank, wherein the mass ratio of the first slurry to the second slurry is 35:65, to obtain a third slurry;

[0102] (4) The third slurry is spray-dried to obtain a lithium iron phosphate precursor yellow material, wherein the inlet air temperature of the spray drying is 230° C. and the outlet air temperature is 96° C.;

[0103] (5) Setting a heating curve, sintering the lithium iron phosphate precursor yellow material in an inert atmosphere, wherein the sintering includes: heating to a sintering temperature, keeping the temperature at the sintering temperature, and then cooling to room temperature, the sintering temperature is 790°C, the heating time is 6h, the keeping time is 7.5h, and the cooling time is 8h. After the sintering is completed, the material is crushed, and the crushing D50 is controlled between 1.1-1.5μm, and D100 is less than 15μm, and the following is obtained: Figure 2 The lithium iron phosphate positive electrode material shown.

[0104] Depend on Figure 1 It can be seen that the lithium iron phosphate positive electrode material prepared in Example 1 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, and the volume ratio of the first particles to the second particles is 54.47:45.53.

[0105] Example 2

[0106] Embodiment 2 provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0107] (1) Fe x PO4, lithium source, carbon source and additives are added to water, the solid content is maintained at 40%, and homogenized and stirred in a dispersion tank, wherein x is 0.955, the lithium source is lithium carbonate, the carbon source is glucose monohydrate, and the additive is titanium dioxide, wherein the molar ratio of Li:Fe (Li in the lithium source and Fe in the carbon source) is 0.955. x The molar ratio of Fe in PO4 is 1.1:1, Fe x The mass ratio of PO4 to carbon source is 1:0.09, and the mass of Ti ions in the additive accounts for 1500ppm of the mass of the finished product LiFePO4. After being evenly dispersed, it is transferred to sand milling, and the average particle size of the sand milled slurry is maintained at 0.35μm to obtain the first slurry;

[0108] (2) Fe x’ PO4, lithium source, carbon source and additives are added to water, the solid content is maintained at 40%, and homogenized and stirred in a dispersion tank, wherein x' is 0.975, the lithium source is lithium carbonate, the carbon source is glucose monohydrate, and the additive is titanium dioxide, wherein the molar ratio of Li:Fe (Li in the lithium source and Fe in the carbon source) is 0.975. x’ The molar ratio of Fe in PO4 is 1.1:1, Fe x’ The mass ratio of PO4 to carbon source is 1:0.11, and the mass of Ti ions in the additive accounts for 1500ppm of the mass of the finished product LiFePO4. After being evenly dispersed, it is transferred to sand milling, and the sand milling particle size is maintained at 0.55μm to obtain the second slurry;

[0109] (3) mixing the first slurry and the second slurry evenly in a finished product tank, wherein the mass ratio of the first slurry to the second slurry is 35:65, to obtain a third slurry;

[0110] (4) The third slurry is spray-dried to obtain a lithium iron phosphate precursor yellow material, wherein the inlet air temperature of the spray drying is 280° C. and the outlet air temperature is 100° C.;

[0111] (5) Setting a heating curve, sintering the lithium iron phosphate precursor yellow material in an inert atmosphere, wherein the sintering includes: heating to a sintering temperature, keeping the temperature at the sintering temperature, and then cooling to room temperature, the sintering temperature is 800°C, the heating time is 6 hours, the keeping time is 7 hours, and the cooling time is 8 hours. After the sintering is completed, the material is crushed, and the crushing D50 is controlled between 1.1-1.5 μm, and D100 is less than 15 μm, so as to obtain Figure 3 The lithium iron phosphate positive electrode material shown.

[0112] Depend on Figure 1 It can be seen that the lithium iron phosphate positive electrode material prepared in Example 2 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, and the volume ratio of the first particles to the second particles is 50.19:49.8.

[0113] Example 3

[0114] Embodiment 3 provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0115] (1) Fe x PO4, lithium source, carbon source and additives are added to water, the solid content is maintained at 40%, and homogenized and stirred in a dispersion tank, wherein x is 0.965, the lithium source is lithium carbonate, the carbon source is glucose monohydrate, and the additive is titanium dioxide, wherein the molar ratio of Li:Fe (Li in the lithium source and Fe in the carbon source) is 0.965. x The molar ratio of Fe in PO4 is 1.1:1, Fe x The mass ratio of PO4 to carbon source is 1:0.11, and the mass of Ti ions in the additive accounts for 3000ppm of the mass of the finished product LiFePO4. After being evenly dispersed, it is transferred to sand milling, and the average particle size of the sand milled slurry is maintained at 0.45μm to obtain the first slurry;

[0116] (2) Fe x’ PO4, lithium source, carbon source and additives are added to water, the solid content is maintained at 40%, and homogenized and stirred in a dispersion tank, wherein x' is 0.970, the lithium source is lithium carbonate, the carbon source is glucose monohydrate, and the additive is titanium dioxide, wherein the molar ratio of Li:Fe (Li in the lithium source and Fe in the carbon source) is 0.970. x’ The molar ratio of Fe in PO4 is 1.1:1, Fe x’The mass ratio of PO4 to carbon source is 1:0.09, and the mass of Ti ions in the additive accounts for 3000ppm of the mass of the finished product LiFePO4. After being evenly dispersed, it is transferred to sand milling, and the sand milling particle size is maintained at 0.48μm to obtain the second slurry;

[0117] (3) mixing the first slurry and the second slurry evenly in a finished product tank, wherein the mass ratio of the first slurry to the second slurry is 35:65, to obtain a third slurry;

[0118] (4) The third slurry is spray-dried to obtain a lithium iron phosphate precursor yellow material, wherein the inlet air temperature of the spray drying is 180° C. and the outlet air temperature is 90° C.;

[0119] (5) Setting a heating curve, sintering the lithium iron phosphate precursor yellow material in an inert atmosphere, wherein the sintering includes: heating to a sintering temperature, keeping the temperature at the sintering temperature, and then cooling to room temperature, the sintering temperature is 770°C, the heating time is 6 hours, the keeping time is 9 hours, and the cooling time is 8 hours. After the sintering is completed, the material is crushed, and the crushing D50 is controlled between 1.1-1.5 μm, and D100 is less than 15 μm, so as to obtain Figure 4 The lithium iron phosphate positive electrode material shown.

[0120] Depend on Figure 1 It can be seen that the lithium iron phosphate positive electrode material prepared in Example 3 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, and the volume ratio of the first particles to the second particles is 48.98:51.02.

[0121] Example 4

[0122] The lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that the additive in step (1) of Example 1 was changed from titanium dioxide to ammonium titanium oxalate.

[0123] Depend on Figure 1 It can be seen that the lithium iron phosphate positive electrode material prepared in Example 4 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, and the volume ratio of the first particles to the second particles is 52.9:47.1.

[0124] Example 5

[0125] The lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that the mass ratio of the first slurry to the second slurry in step (3) of Example 1 was changed to 30:70.

[0126] Depend on Figure 1It can be seen that the lithium iron phosphate positive electrode material prepared in Example 5 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, and the volume ratio of the first particles to the second particles is 54.48:45.52.

[0127] Example 6

[0128] The lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that the mass ratio of the first slurry to the second slurry in step (3) of Example 1 was changed to 40:60.

[0129] Comparative Example 1

[0130] The lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that the sintering temperature in Comparative Example 1 was 810°C.

[0131] Comparative Example 2

[0132] A lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that the grinding particle sizes of the first slurry and the second slurry in Comparative Example 2 were both 0.4 μm.

[0133] The lithium iron phosphate positive electrode material obtained in Comparative Example 2 is as follows Figure 7 shown.

[0134] Comparative Example 3

[0135] A lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that the grinding particle sizes of the first slurry and the second slurry in Comparative Example 3 were both 0.5 μm.

[0136] Depend on Figure 1 It can be seen that the lithium iron phosphate positive electrode material prepared in Comparative Example 3 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, the volume ratio of the first particles to the second particles is 60.05:39.95, and the volume proportion of the first particles is relatively too large.

[0137] Comparative Example 4

[0138] The lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that: Fe x PO4 x and Fe in the second slurry x’ The x' of PO4 is 0.960.

[0139] Comparative Example 5

[0140] The lithium iron phosphate positive electrode material was prepared according to the steps of Example 1. The other steps were the same as those of Example 1, except that: Fe x PO4 x and Fe in the second slurry x’ The x' of PO4 is 0.970.

[0141] The lithium iron phosphate positive electrode material obtained in Comparative Example 5 is as follows Figure 8 shown.

[0142] Depend on Figure 1 It can be seen that the lithium iron phosphate positive electrode material prepared in Comparative Example 5 includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, the particle size of the second particles is greater than 1 μm, the volume ratio of the first particles to the second particles is 70.42:29.58, and the volume proportion of the first particles is too large.

[0143] The positive electrode materials prepared in the examples and comparative examples were mixed with PVDF and NMP at a ratio of 90:5:5 to prepare positive electrode slurry, which was coated on aluminum foil, and then punched and sheared after drying to obtain positive electrode plates. The button cells were assembled in a glove box, and the positive electrode plates were assembled with lithium sheets, diaphragms, and electrolytes into button cells. The assembled button cells were placed in the mold groove of a hydraulic sealing machine, locked, pressed, and then unlocked to take out the sealed button cells. The diaphragm was a Celgard polypropylene film, and the electrolyte was purchased from Guangzhou Tianci.

[0144] The test was carried out using a Lanhe (model: CT3002A) battery test cabinet with a test voltage range of 2.0V to 3.75V. Specifically, the battery was charged to 3.75V at a constant current of 0.1C, charged to 50μA at a constant voltage, and discharged to 2.0V at 0.1C, which was regarded as the first activation cycle. Again, the battery was charged to 3.75V at a constant current of 1C, charged to 50μA at a constant voltage, and discharged to 2.0V at 1C, and the discharge capacity after the second cycle was recorded.

[0145] The test results are shown in Table 1.

[0146] Table 1 Comparison of compaction density and discharge gram capacity of positive electrode materials of Examples and Comparative Examples

[0147] <![CDATA[Compaction density (g / cm 3 )]]> 1C discharge capacity (mAh / g) Example 1 2.521 146.56 Example 2 2.505 147.34 Example 3 2.512 143.28 Example 4 2.485 148.49 Example 5 2.501 145.06 Example 6 2.492 142.96 Comparative Example 1 2.480 138.25 Comparative Example 2 2.452 137.78 Comparative Example 3 2.445 140.96 Comparative Example 4 2.475 137.09 Comparative Example 5 2.465 145.10

[0148] It can be seen from Examples 1-6 and Comparative Examples 2-3 that, compared with Comparative Examples 2-3, Examples 1-6 have both higher compaction density and higher gram capacity, indicating that the particle size matching method of the present application can take into account both compaction and capacity performance.

[0149] It can be seen from Examples 1-6 and Comparative Examples 4-5 that, compared with Comparative Examples 4-5, Examples 1-6 have both higher compaction density and higher gram capacity, indicating that the iron-phosphorus ratio matching method of the present application can take into account both compaction and capacity performance.

[0150] As described above, the technical solution of the present invention brings into play the synergistic effect of the iron-phosphorus ratio matching method and the particle size matching method, optimizes the particle size distribution, improves the stacking density and compaction density, and at the same time improves the kinetic properties such as discharge capacity, thereby achieving significant technical effects.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0152] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a high-density lithium iron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: Fe x PO4 is mixed with a lithium source, a carbon source, an additive, and water to obtain a first mixture, and sand-milled to obtain a first slurry, wherein x is 0.955 to 0.965; Fe x’ PO4 is mixed with a lithium source, a carbon source, an additive, and water to obtain a second mixture, and sand-milled to obtain a second slurry, wherein the particle size of the second slurry is greater than the particle size of the first slurry, x'>x, x' is 0.965 to 0.980, preferably 0.970 to 0.975; Mixing the first slurry with the second slurry to obtain a third slurry; The third slurry is spray-dried to obtain a lithium iron phosphate precursor yellow material; The lithium iron phosphate precursor yellow material is sintered and crushed to obtain a high-density lithium iron phosphate positive electrode material.

2. The method for preparing a high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The particle size of the first slurry is 0.35-0.45 μm, and the particle size of the second slurry is 0.45-0.55 μm, preferably 0.48-0.55 μm.

3. The method for preparing a high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide; The carbon source includes a carbon-based material or a hydrate of a carbon-based material, and the carbon-based material includes at least one of PEG, citric acid, glucose, PVP, and sucrose; The additive includes at least one of titanium dioxide, ammonium titanium oxalate, vanadium pentoxide, ammonium metavanadate, and manganese acetate.

4. The method for preparing a high-density lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: When the first mixture is formed, the Li in the lithium source and the Fe x The molar ratio of Fe in PO4 is (1.0-1.1):1; And / or, when forming the first mixture, the Fe x The mass ratio of PO4 to the carbon source is 1:(0.05-0.15), preferably 1:(0.09-0.11); and / or, when forming the first mixture, the mass of the metal cations in the additive accounts for 100-3000 ppm, preferably 1500-3000 ppm, of the mass of the finished lithium iron phosphate material; And / or, when forming the second mixture, the Li in the lithium source and the Fe x’ The molar ratio of Fe in PO4 is (1.0-1.1):1; And / or, when forming the second mixture, the Fe x’ The mass ratio of PO4 to the carbon source is 1:(0.05-0.15), preferably 1:(0.09-0.11); And / or, when forming the second mixture, the mass of the metal cations in the additive accounts for 100-3000 ppm, preferably 1500-3000 ppm, of the mass of the finished lithium iron phosphate material.

5. The method for preparing a high-density lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The mass ratio of the first slurry to the second slurry is (1-100):(100-1), preferably (30-40):(60-70).

6. The method for preparing a high-density lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The inlet air temperature of the spray drying is 180-280°C, and the outlet air temperature of the spray drying is 90-100°C.

7. The method for preparing a high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The sintering comprises: heating to a sintering temperature, keeping the temperature at the sintering temperature, and then cooling to room temperature, the sintering temperature is 700°C to 800°C, preferably 770°C to 790°C, the heating time is 5 to 9 hours, the keeping time is 7 to 10 hours, and the cooling time is 8 to 10 hours; The sintering is performed in an inert atmosphere.

8. A high-density lithium iron phosphate positive electrode material, characterized in that: The high-density lithium iron phosphate positive electrode material is prepared by the preparation method of the high-density lithium iron phosphate positive electrode material according to any one of claims 1 to 7.

9. A high-density lithium iron phosphate positive electrode material, characterized in that: The high-density lithium iron phosphate positive electrode material includes first particles and second particles, the particle size of the first particles is less than or equal to 1 μm, and the particle size of the second particles is greater than 1 μm; And / or, the volume ratio of the first particles to the second particles is (40-60):(60-40); And / or, the first particle comprises Li 1.0-1.1 Fe x’ PO4, where x' is 0.965 to 0.980 ; And / or, the second particle comprises Li 1.0-1.1 Fe x PO4, wherein x is 0.955 to 0.

965.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the high-density lithium iron phosphate positive electrode material according to claim 8 or 9.

Citation Information

Patent Citations

  • High-compaction lithium iron phosphate material and preparation method thereof

    CN111217347A

  • Preparation method of high-compaction lithium iron phosphate

    CN111392705A

  • High-compaction-density lithium iron phosphate and preparation method thereof

    CN113562714A

  • Preparation method of lithium iron phosphate, positive active material, positive pole piece, battery and electric device

    CN117088352A

  • Phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN117594792A

Cited By

  • High-rate lithium iron phosphate positive electrode material, preparation method thereof and battery

    CN120136068A

  • High-compaction lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN120841472A

  • Secondary sintering process method for improving compaction density of lithium iron phosphate and application of secondary sintering process method

    CN121317679A

  • Preparation method of high-compaction-density lithium iron phosphate positive electrode material

    CN121470453A